Factors associated with adults' perceived need to vaccinate against hepatitis B in rural China. Issue 5 (3rd May 2016) - Yu, Lijie; Wang, Jian; Wangen, Knut R.; Chen, Ruohan; Maitland, Elizabeth; Nicholas, Stephen
ABSTRACT: Hepatitis B virus (HBV) infection is a serious public-health issue in China. While the hepatitis B vaccine is effective in preventing HBV infection, the HBV vaccination coverage rates among Chinese adults remain low. From a survey of rural adults from 7 provinces in China, we identified a unique HBV at-risk group: rural adults who had no history of HBV vaccination and had no plan to HBV vaccinate in the future. We divided this 'no history-no plan' group into those who identified No-need to vaccinate and those that perceived a Need to vaccinate (even if they had no plan to do so). We found age, marital status, health status, perceived HBV infection environment, perceived HBV infection risk and perceived HBV infection severity explained differences between the 'No-need' and 'Need" to HBV vaccinate groups. Education, occupation and knowledge of hepatitis B and HBV transmission were not associated with HBV vaccination need. Our results showed that free HBV vaccinations and reimbursement for vaccinating could significantly increase the HBV vaccinate take-up rate for both Need and No-need rural adults. A tailored public health HBV campaign, especially targeting the No-need subgroup, would increase vaccination rates by better informing rural adults about HBV transmission routes, the dangers of HBV infection, the effectiveness of HBV vaccinations and the safety of HBV vaccinations.